Metadynamic recrystallization of Nb–V microalloyed steel during hot deformation. Issue 3 (3rd January 2017) - Shen, Wen-fei; Zhang, Chi; Zhang, Li-wen; Xia, Ying-nan; Xu, Yi-feng; Shi, Xin-hua
Abstract: Abstract : The metadynamic recrystallization (MDRX) behavior of a Nb–V microalloyed nonquenched and tempered steel was investigated by isothermal hot compression tests on Gleeble-1500 thermal-mechanical simulator. Compression tests were performed using double hit schedules at temperatures of 1273–1423 K, strain rates of 0.01–5 s −1, initial grain sizes of 92–149 μm and an inter-pass time of 0.5–10 s. The experimental results show that MDRX softening fraction increases with the increasing of deformation temperature, strain rate, and inter-pass time, while it decreases with the increasing of initial grain size. Based on the experimental results, the MDRX softening fraction kinetic model and recrystallized grain size model of the tested steel was established. Besides, using the above mathematic models, a finite element model was built to simulate the MDRX process of the tested steel. The simulation results show good agreement with the experimental ones, which indicates that finite element method is an effective approach to analyze the MDRX behavior and the established that mathematic models of the tested steel are reliable and accurate.